Análise de balanceamento em uma linha de montagem de motores: um estudo aplicado - Botelho, Vitor dos Santos Belo (2019)
With globalization, the business landscape is becoming increasingly competitive. That is also why Aiming at this scenario, this work intends to analyze and propose improvements in the engine assembly process of an automaker located in Paraná. In order to achieve this objective, the process was mapped through a study of time and methods, with a more precise tool for chronological analysis and definition of the characteristics and restrictions of the line. Concepts of lean manufacturing were used and with the information obtained, alternatives were developed for a new balancing of the line, making use of the maximum efficiency of resources and also the calculation of capacity. Along with these proposals, we also analyzed the gain in displacement reduction, thus reducing the activities that do not aggregate value to the process.